The Crux Interpretum of 1 Cor 15:29: What is at Stake and a Proposal - Bianchini, Francesco (Verbum Vitae, 2022)
This short paper tackles the much-discussed crux interpretum of 1 Cor 15:29. Biblical scholars have tended to analyse word for word the expression οἱ βαπτιζόμενοι ὑπὲρ τῶν νεκρῶν and present various hypotheses, with the idea favored by the scholarly majority being that of vicarious baptism for the dead. I propose a new reading of 1 Cor 15:29 in its literary and rhetorical context of 1 Cor 15:12–34. Here, what those who believe in Christ do (v. 29), what the apostles do (v. 30), and what Paul does (vv. 31–32), are put together as good practices which become incomprehensible if there is no resurrection of the dead. Vicarious baptism cannot be considered a good practice because it is at odds with Paul’s concept of baptism, and because it was later even considered heretical and aberrant. In this context, the paper proposes to read ὑπέρ with a sense of finality, i.e. “for/in view of,” and to see in ὑπὲρ τῶν νεκρῶν a brachylogy (as Paul employs elsewhere in his letters) for “for/in view of the resurrection of the dead.” Therefore in 1 Cor 15:29 Paul presents the positive example of the people who undergo baptism as a public manifestation of faith, in the hope of taking part in the final resurrection together with all the dead, especially with those who are “in Christ.” To the new reading corresponds this new translation: “Otherwise, what will they do those who have themselves baptised for/in view of (the resurrection of) the dead? If the dead are not raised at all, why then do they have themselves baptized for/in view of (the resurrection of) them?”